The ambulatory transoral endoscopic thyroidectomy vestibular approach is safe and economical for patients with thyroid nodules - Sun, Haiqing; Chu, Yongli; Zhang, Guojun; Zheng, Guibin; Zheng, Haitao (Frontiers in Endocrinology, 2023)
Background: Ambulatory thyroid surgery has been increasingly performed in recent years. However, the feasibility of the ambulatory transoral endoscopic thyroidectomy vestibular approach (TOETVA) has not been evaluated. We aimed to evaluate the safety, economy, and mental health outcomes of ambulatory TOETVA. Methods: We retrospectively reviewed the data of patients who underwent TOETVA between March 2019 and August 2022. The procedure was performed by a skilled surgical team from the Department of Thyroid Surgery of the affiliated Yantai Yuhuangding Hospital of Qingdao University. Patients were enrolled in the ambulatory (n=166) and conventional (n=290) groups, based on their chosen procedure. We analyzed patients’ clinical characteristics, surgical outcomes, Hamilton Anxiety Rating Scale (HAM-A) scores, and hospitalization costs. Results: Of 456 patients, 166 underwent ambulatory TOETVA and 290 underwent conventional TOETVA. No significant differences were found in clinical and surgical characteristics between the groups, including sex (P=0.363), age (P=0.077), body mass index (P=0.351), presence of internal diseases (P=0.613), presence of Hashimoto’s thyroiditis (P=0.429), pathology (P=0.362), maximum tumor diameter (P=0.520), scope of surgery (P=0.850), or operative time (P=0.351). There were no significant differences in maximum tumor diameter (P=0.349), extrathyroidal tissue invasion (P=0.516), number of retrieved central lymph nodes (P=0.069), or metastatic central lymph nodes (P=0.897) between the groups. No significant differences were found in complications, including transient hypoparathyroidism (P=0.438), transient vocal cord palsy (P=0.876), transient mental nerve injury (P=0.749), permanent mental nerve injury (P=0.926), and other complications (P=1.000). Ambulatory patients had shorter hospital stays (P<0.001) and reduced hospitalization costs (P<0.001). There was no significant difference in HAM-A scores between the groups (P=0.056). Conclusions: Ambulatory TOETVA is a safe, feasible, and cost-effective procedure for selected patients. This procedure resulted in shorter hospital stays, decreased medical costs, and did not increase patient anxiety. To ensure patient safety, surgical teams must inform patients of the indications, when to seek help, and how to receive the fastest medical attention.